Corporate governance and earnings management: Does gender matter? - Ria Karina (Jurnal Akuntansi dan Auditing Indonesia, 2021)
This study aims to analyse the extent to which corporate governance is able to influence earnings management when moderated by the presence of woman in board of directors. Independent variables used in this study were board independence, board meeting, board size, managerial ownership, ownership concentration, institutional ownership, audit quality, and firm size. This study used the financial data from the companies that are registered in Indonesia Stock Exchange from 2015-2019. The total 1,749 data were tested using multiple linear regression analysis. The results show that board independence has significantly positive effect, while firm size have negatively significant effect on earnings management when the relationship is moderated by board gender diversity. The other variables do not show significant results. This study contributes to the provision of inputs to the literature development related to governance idea proposing that the woman factor in governance can be important for the company control. In addition, this study has the implication for companies to analyse good corporate governance and consider the role of woman in the company management.